Effect of repetitive activity upon intracellular pH, sodium and contraction in sheep cardiac Purkinje fibres. - Bountra, C; Kaila, K; Vaughan-Jones, R (1988)
1. The influence of repetitive activity upon intracellular pH (pHi), intracellular Na+ activity (aNA(i)) and contraction was examined in isolated sheep cardiac Purkinje fibres. Ion-selective microelectrodes were used to measure intracellular Na+ and H+ ion activity. Twitch tension was elicited by field stimulation or by depolarizing pulses applied using a two-microelectrode voltage clamp. Experiments were performed in HEPES-buffered solution equilibrated either with air or 100% O2. 2. An increase in action potential frequency from a basal rate of 0.1 to 1-4 Hz induced a reversible fall in pHi and a reversible rise in aNa(i). These effects reached a steady state 3-10 min following an increase in stimulation frequency, and showed a linear dependence on frequency with a mean slope of 0.023 pH units Hz-1 and 0.57 mmol l-1 Hz-1, respectively. The rise in total intracellular acid and aNa(i) associated with a single action potential was estimated as 5.3 mu equiv l-1 of acid and 3.5 mu equiv l-1 of Na+. 3. At action potential frequencies greater than 1 Hz, the rate-dependent rise in aNa(i) was usually accompanied by a positive force staircase. 4. The fall in pHi following a rate increase also occurred when fibres were bathed in Tyrode solution equilibrated with 23 mM-HCO3- plus nominally 5% CO2/95% O2. In these cases, however, the fall in pHi was halved in magnitude. 5. In fibres exposed to strophanthidin (0.5 microM), the rate-dependent fall in pHi was doubled in magnitude and its time course was more variable than under drug-free conditions. The rate-dependent rise in aiNa was also usually larger in strophanthidin. 6. In order to examine the influence of the rate-dependent acidosis on developed tension, the acidosis was reversed experimentally by adding 2 mmol l-1 NH4Cl to the bathing solution. This produced a rise in pHi accompanied by a large increase in twitch tension. Such an effect of pHi upon tension was quantitatively similar to that observed in previous work on Purkinje fibres (Vaughan-Jones, Eisner and Lederer, 1987). 7. It is concluded that the rate dependence of pHi will influence both the magnitude and the time course of an inotropic response to a change in heart rate.